Case report: Personalized computational model guided ablation for left atrial flutter - Lange, Matthias; Kwan, Eugene; Dosdall, Derek J.; MacLeod, Rob S.; Bunch, T. Jared; Ranjan, Ravi (Frontiers in Cardiovascular Medicine, 2022)
Atypical atrial flutter is seen post ablation in patients, and they can be challenging to map. These flutters are typically set up around areas of scar in the left atrium. MRI can reliably identify left atrial scar. We propose a personalized computational model using patient specific scar information, to generate a monodomain model. In the model conductivities are adjusted for different tissue regions and flutter was induced with a premature pacing protocol. The model was tested prospectively in patients undergoing atypical flutter ablation. Simulation predicted flutters were visualized and presented to clinicians. Validation of the computational model was motivated by recording from electroanatomical mapping. These personalized models successfully predicted clinically observed atypical flutter circuits and at times even better than invasive maps leading to flutter termination at isthmus sites predicted by the model.